BIRTH OUTCOMES OF MATERNAL MORBID OBESITY - JOEWONO, HERMANTO TRI; SULISTYONO, AGUS; KARTININGSIH, NI KETUT ANNY; ADITIAWARMAN (International Journal of Psychosocial Rehabilitation, 2020)
Background: The prevalence of pregnancy with morbid obesity has increased in the last decade which caused complications for both the mother and fetus. The aim of this study was to find out the birth outcomes of pregnant women with morbid obesity who gave birth at Dr. Soetomo General Hospital, Surabaya from 2013 to 2015.Methods: This was a descriptive study on pregnant women with morbid obesity (BMI ≥40 kg /m2) who gave birth in the delivery room of Dr. Soetomo General Hospital, Surabaya from January 2013 to June 2015.Results: There were 3986 deliveries during the study period with 297 (7.4%) deliveries with obese mothers. The births with morbid obesity were in 42 mothers (14%). The range of BMI was 40.17-59 kg/m2 with median of 45.86 kg/m2. Caesarean section was the most mode of delivery in mothers with morbid obesity as many as 36 mothers (85%). The options of anesthesy in mother with morbid obesity were general anesthesia and subarachnoid block, 9 (25%) and 27 (75%), respectively. The childbirth in mother with morbid obesity spend an average of 69.60 minutes for cesarean delivery with the average time of incision until the birth of a baby 8.67 minutes. Most Apgar score group of infant was in 7-10 group.Conclusion: The birth outcomes of morbidly-obese pregnant women were caesarean section delivery, long duration in delivery, and normal birth weight.